Frequency of Hyperuricemia in Patients with Controlled and Uncontrolled Hypertension - Tasneem Jaweid; Salma Razzaque; Ajeet Kumar; Marium Marufia Khan; Faiza Zaib (Journal of Liaquat University of Medical & Health Sciences, 2026)
OBJECTIVE: To compare the frequency of hyperuricemia between controlled and uncontrolled hypertensive patients. METHODOLOGY: A cross-sectional study was done by the Department of Medicine at Sohail Trust Hospital Karachi, an associated hospital of Jinnah Medical & Dental College, from December 2024 to March 2025. The study employed non-probability consecutive sampling and involved a sample size of 150 participants. Informed consent was obtained from patients who met the inclusion criteria. Data were entered in the performa. Data analysis was performed using SPSS version 26.0. The Chi-square test was used to compare hyperuricemia between controlled and uncontrolled hypertensive patients at a 5% level of significance, and a P-value ? 0.05 was considered statistically significant. RESULTS: Mean ± SD of age was 56.11±8.75 years. Mean ± SD of serum uric acid (SUA) was 7.44±2.27 mg/dl. 112 (74.7%) were male, while 38 (25.3%) were female patients. Controlled hypertension was present in 49 (32.7%), while uncontrolled hypertension was present in 101 (67.3%) patients. Hyperuricemia was found in 107 (71.3%) patients, among them 35 (23.3%) had controlled hypertension, while 72 (48.0%) had uncontrolled hypertension, and the p-value was determined as not statistically significant (P=0.986). CONCLUSION: Hyperuricemia was highly prevalent in our population, although no significant association was observed between SUA levels and blood pressure control status. Larger multicenter studies with broader clinical parameters are recommended to explore this association further and determine its clinical significance.